Increasing Student Creativity Through the Development of Life Skills-Based Graphic Design Textbooks: Peningkatan Kreativitas Mahasiswa Melalui Pengembangan Buku Ajar Desain Grafis Berbasis Kecakapan Hidup - Marandy, Yuniar Setyo (Universitas Muhammadiyah Sidoarjo, 2023)
The development of a graphic design textbook based on life skills for students of the Tarbiyah and Teacher Training Faculty of UIN Maulana Malik Ibrahim Malang is one of the means to help students understand and improve their pedagogical and creative abilities. This research and development aimed to (1) describe the process of developing a life skills-based graphic design textbook for students, (2) determine the level of attractiveness of life skills-based graphic design for students, and (3) determine the effect of life skills-based graphic design for students. This research and development method uses research and development (R&D) research. The procedure for developing this research uses a model, namely the Borg and Gall model. This research was conducted at the Faculty of Tarbiyah and Teacher Training UIN Maulana Malik Ibrahim Malang. Data collection techniques in this study were tests and observations. The data obtained were analyzed quantitatively and qualitatively. The results of the development carried out were in the form of a book